The athlete's clock how biology and time affect sport performance - Rowland, Thomas W. (Human Kinetics, 2011)
In this exceptionally readable exploration of athletic achievement, the author draws practical conclusions from science and experience to describe how various aspects of time affect sport performance. Readers can investigate challenging questions such as whether athletes consciously control sport performance, how young athletes can be safely nurtured to greatness, and what the optimal time of day is for training. This book takes you on a wide-ranging journey into the complexity and beauty of the human body in motion. It will forever change the way you watch and participate in sport as you come to realize it's all in the timing. -- from Back Cover